Weak Pseudo â€“ 2 â€“ Absorbing Submodules And Related Concepts - Mohmmadal, Haibat K.; Radeef, Sada E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Let  R  be a commutative ring  with identity  and  E  be a unitary left  R â€“ module .We introduce  and study the concept Weak Pseudo â€“ 2 â€“ Absorbing submodules as  generalization of weakle â€“ 2 â€“ Absorbing submodules , where a proper submodule  A of  an  R â€“ module  E is  called  Weak Pseudo â€“ 2 â€“ Absorbing  if   0 â‰  rsx   A   for  r, s  R , x  E , implies that  rx   A + soc ( E ) or  sx  A + soc (E)  or   rs  [ A + soc ( E ) E ]. Many basic  properties, characterizations  and  examples  of   Weak Pseudo â€“ 2 â€“ Absorbing  submodule  in some  types  of  modules  are  introduced .